Gambaran Pelaksanaan Standar Pelayanan Minimal (SPM) Gizi Di BLUD Rumah Sakit Konawe Tahun 2022 - Saasa; Thamrin Datjing; Nirwana; La Ode Taalami; Guntur; La Ode Liaumin Azim (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat (LPPM), Institut Teknologi Dan Kesehatan (ITK) Avicenna, 2022)
Background: Food service is part of the hospital's nutrition service system, which consists of menu planning and distribution of food to patients in order to achieve optimal health status through proper diet. Objective: This study aims to identify and describe menu planning, food procurement, food storage, and food distribution to patients at the BLUD Konawe Hospital. Methods: This research is an ex post facto study with a survey approach to 30 sample people who are nutrition installation staff at the BLUD Konawe Hospital using questionnaire sheet instruments and observation forms related to menu planning, food procurement, food storage, and food distribution to patients from 15 July to 15 August 2022. Data analysis used univariate analysis. Results: Menu planning was in the poor category with a percentage of 76.7%, food procurement was very good with a percentage of 86.7%, food storage was in the good category with a percentage of 76, 7%, the distribution of food is in the very good category with a percentage of 86.7%. Conclusion: The implementation of food in the nutrition installation shows that the menu planning variables are in the poor category, the procurement of food ingredients, the storage of food ingredients, and the distribution of food for patients are included in the good category